Da'wah and Democracy: Actualization of the Role of Religion in State Behavior - Ahmad Zuhdi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
This study aims to analyze the role of da'wah as the actualization of the role of religion in democratic behavior. Specifically, the research is focused on exploring the actualization of Islamic values in democratic behavior in Indonesia. The researcher tries to describe the dimensions of state da'wah, especially its relation to democracy. This research was conducted with a qualitative approach through a literature study. The results show that the existence of a state (daula) in people's lives is an essential entity to build a collective moral order. The role of religion supports Islamic da'wah activism, which is carried out both with a cultural and structural approach. Islamic da'wah activities are carried out to control democratic behavior in the administration of a country's government. State da'wah activities are carried out to embody Amar maruf nahi munkar. Efforts to implement Islamic da'wah in applying the principles of state democracy must function as a social control over state administrators to always pay attention to the mandate of their leadership.